Implementing patient navigation programs: Considerations and lessons learned from the Alliance to Advance Patient‐Centered Cancer Care. Issue 14 (17th May 2022) - Ver Hoeve, Elizabeth S.; Simon, Melissa A.; Danner, Sankirtana M.; Washington, Antonio J.; Coples, Susan D.; Percac‐Lima, Sanja; Whited, Emma C.; Paskett, Electra D.; Naughton, Michelle J.; Gray, Darrell M.; Wenzel, Jennifer A.; Zabora, James R.; et al.
Abstract : Background: Six multidisciplinary cancer centers were selected and funded by the Merck Foundation (2017‐2021) to collaborate in the Alliance to Advance Patient‐Centered Cancer Care ("Alliance"), an initiative to improve patient access, minimize health disparities, and enhance the quality of patient‐centered cancer care. These sites share their insights on implementation and expansion of their patient navigation efforts. Methods: Patient navigation represents an evidence‐based health care intervention designed to enhance patient‐centered care and care coordination. Investigators at 6 National Cancer Institute‐designated cancer centers outline their approaches to reducing health care disparities and synthesize their efforts to ensure sustainability and successful transferability in the management of patients with cancer and their families in real‐world health care settings. Results: Insights are outlined within the context of patient navigation program effectiveness and supported by examples from Alliance cancer center sites: 1) understand the patient populations, particularly underserved and high‐risk patients; 2) capitalize on the existing infrastructure and institutional commitment to support and sustain patient navigation; and 3) build capacity by mobilizing community support outside of the cancer center. Conclusions: This process‐level article reflects the importance of collaboration and the usefulness of partnering with other cancer centers to share interdisciplinary insights while undergoing intervention development, implementation, and expansion. These collective insights may be useful to staff at other cancer centers that look to implement, enhance, or evaluate the effectiveness of their patient navigation interventions. Abstract : The Alliance to Advance Patient‐Centered Cancer Care shares 3 insights for cancer care centers looking to implement effective patient navigation programs. These insights include: 1) understanding the cancer center's catchment area, 2) capitalizing on the existing infrastructure, and 3) mobilizing community support.